Pharmacokinetic profiles of three dose rates of morphine sulfate following single intravenous, intramuscular, and subcutaneous administration in the goat. Issue 1 (7th September 2021) - Gordon, Emma; Dirikolu, Levent; Liu, Chin‐Chi; Ulanov, Alexander V.; Li, Zhong; Welborn, Matt; Armstrong, Chance; Vallotton, Danielle; Keeton, Sarah; Camlic, Sarah; Scully, Clare M.
Abstract: This study aimed to evaluate pharmacokinetic profiles of morphine in goats following a single dose administered intravenously, intramuscularly, or subcutaneously at 0.1 mg/kg, 0.25 mg/kg, and 0.4 mg/kg. Study population included eight healthy adult goats in a randomized cross‐over study. Serial plasma samples were collected and morphine was quantified using high‐performance liquid chromatography/mass spectrometry. Data fit a two‐compartment model following intravenous administration and a non‐compartmental model following both intramuscular and subcutaneous administration. Plasma elimination half‐life was 2.88 ± 1.13 h (0.1 mg/kg), 2.30 ± 0.49 h (0.25 mg/kg), and 2.67 ± 0.82 h (0.4 mg/kg) following IV morphine. Intramuscular Cmax values were 13.4 ± 2.77 ng/ml (0.1 mg/kg), 34 ± 11.50 ng/ml (0.25 mg/kg), and 68.9 ± 24.5 ng/ml (0.4 mg/kg). Intramuscular Tmax f(h) or IM dosing (in hrs) was 0.19 ± 0.14 (0.1 mg/kg), 0.24 ± 0.24 (0.25 mg/kg), and 0.21 ± 0.24 (0.4 mg/kg). Subcutaneous Cmax values were 9.88 ± 3.31 ng/ml (0.1 mg/kg), 28.5 ± 11.6 ng/ml (0.25 mg/kg), and 39.4 ± 14.3 ng/ml (0.4 mg/kg). Subcutaneous Tmax (h) values for SC dosing were 0.36 ± 0.21 (0.1 mg/kg), 0.31 ± 0.17 (0.25 mg/kg), and 0.4 ± 0.13 (0.4 mg/kg). Intramuscular bioavailability values were 153.77 ± 12.60% (0.4 mg/kg), 104.8 ± 25.12% (0.25 mg/kg), and 100.7 ± 29.57% (0.1 mg/kg). Subcutaneous bioavailability values were 130.58 ± 19.07% (0.4 mg/kg), 116.6 ± 27.03% (0.25 mg/kg), and 111.6 ± 23.24% (0.1 mg/kg). No adverse effects were observed. Assuming plasma concentration required to induce analgesia is 16 ± 9 ng/ml in goats, as demonstrated in humans, it is suggested to administer morphine intramuscularly at 0.4 mg/kg every 3–4 h or SC every 2–3 h. This is a speculative conclusion therefore further studies evaluating pharmacodynamics and plasma analgesic threshold in goats is recommended.